Proliferation resistance evaluation of CANDU reactor systems with different fuel cycles - Wang, Xiaopan (My University, 2016)
In the process of exploring the thorium fuel application in CANDU reactors, it is important to consider the proliferation resistance level as a parameter for comparison with current natural uranium fuel. The concept of a whole fuel cycle was introduced to show the variations in the proliferation resistance level as the material is flowing through the cycle. The depletion and decay histories were simulated with SCALE 6.1 code and the results such as isotopes composition, decay heat, and radioactivity were used to analyze the material attractiveness of pure heavy metal for weapon production. They also served as the intrinsic features during the proliferation resistance level calculation. The Multi-Attribute Utility Analysis (MAUA) method developed by Chalton was used to compare different CANDU fuel cycles with quantified values (PR) from the viewpoint of proliferation resistance. To improve the biased MAUA results that gave a PR of 0.76 to CANDU while 0.93 to PWR, the attributes of size/weight and refueling scheme were reconsidered. In addition, the sensitive technology involved was added for the proliferation resistance recalculation. The results showed an increased PR value of 0.82 for natural uranium CANDU reactor as well as a decreasing trend of PR at the back end. PWR has a PR of 0.82 with revised MAUA method. The PR comparison of thorium and natural uranium fuel indicated that Th/Pu fuel has a slightly higher PR value in the reactor. The Figure of Merit (FOM) method developed by Bathke was used to validate the PR results from another perspective: the attractiveness of pure heavy metals that are suitable for nuclear weapon production. The results showed that FOM of plutonium keeps increasing with decay time and the trend becomes more significant after disposal in the deep geological repository. The FOM of uranium from Th/Pu cases is higher than that of Pu within several hundred years but maintains a decreasing trend. The decreasing FOM of uranium is preferred for direct disposal in deep geological repository. The decreased PR level and the increased FOM value of plutonium at the back end of a fuel cycle indicate the importance of implementing the security and safeguard for each facility dealing with nuclear materials. The comparison results of PR and FOM values for different fuel provided feedback and suggestions for the new fuel application.
Keywords: proliferation resistance; CANDU; fuel cycle; thorium application